Traditions, Traps and Tricks. Social aspects of the Transfer of Inuit qaujimajatuqangit - Laugrand, Frédéric; Oosten, jarich (The University of Alberta Press, 2018)
The transfer of knowledge is a key issue in the North as Indigenous Peoples meet the ongoing need to adapt to cultural and environmental change. In eight essays, experts survey critical issues surrounding the knowledge practices of the Inuit of northern Canada and Greenland and the Northern Sámi of Scandinavia, and the difficulties of transferring that knowledge from one generation to the next. Reflecting the ongoing work of the Research Group Circumpolar Cultures, these multidisciplinary essays offer fresh understandings through history and across geography as scholars analyze cultural, ecological, and political aspects of peoples in transition. Traditions, Traps and Trends is an important book for students and scholars in anthropology and ethnography and for everyone interested in the Circumpolar North. Contributors: Cunera Buijs, Frédéric Laugrand, Barbara Helen Miller, Thea Olsthoorn, Jarich Oosten, Willem Rasing, Kim van Dam, Nellejet Zorgdrager